SIMULAÇÕES TÉRMICAS E LUMÍNICAS APLICADAS EM PROJETO DE EDIFÍCIOS COMERCIAL - Garcia, Dayan de Loyola R.; Silveira, Vinicius de Castro; Pereira, Fernando O. Ruttkay Pereira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Nowadays buildings' industry, designers, engineers and architects still enhancing the methods and metrics to measure the building performance. In this context, this paper has objective to spread currently computational tools that evaluate the thermal and luminous environment during design stages in commercial buildings projects. Daylight Autonomy and Useful Daylight Illuminance were metrics used by DIVA 4.0 for Rhino to measure daylighting differences between models that vary glazing materials and window-to-wall ratio. Results show that large fenestration doesn't work well without shading devices or complex glazing systems. The thermal performance, utilizing different materials, was simulated using EnergyPlus software. It was possible to observe in the results that, the material with greater capacity of thermal inertia (masonry of seal), presented more satisfactory results maintaining greater constancy on internal temperature. The presented tools and metrics are being utilized in certification's process, like in LEED v4. At the same time, bests design's options and warnings can be found through easier functions offered by presented means.